2012
DOI: 10.1007/s00382-012-1386-0
|View full text |Cite
|
Sign up to set email alerts
|

A possible cause of the AO polarity reversal from winter to summer in 2010 and its relation to hemispheric extreme summer weather

Abstract: In 2010, the Northern Hemisphere, in particular Russia and Japan, experienced an abnormally hot summer characterized by record-breaking warm temperatures and associated with a strongly positive Arctic Oscillation (AO), that is, low pressure in the Arctic and high pressure in the midlatitudes. In contrast, the AO index the previous winter and spring (2009/2010) was record-breaking negative. The AO polarity reversal that began in summer 2010 can explain the abnormally hot summer. The winter sea surface temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Because chaotic phase variations of the Silk Road pattern are not strongly tied to SST forcing, it limits the predictability at monthly and longer leads over East Asia even though the PJ pattern transmits predictable tropical influences. Some recent studies, however, suggest an association of the Silk Road pattern with Atlantic SST (Wu et al, 2009b;Yamaura and Tomita, 2011;Otomi et al, 2013). This is a potential source of predictability that can benefit midlatitude Asian countries.…”
Section: Midlatitudesmentioning
confidence: 99%
“…Because chaotic phase variations of the Silk Road pattern are not strongly tied to SST forcing, it limits the predictability at monthly and longer leads over East Asia even though the PJ pattern transmits predictable tropical influences. Some recent studies, however, suggest an association of the Silk Road pattern with Atlantic SST (Wu et al, 2009b;Yamaura and Tomita, 2011;Otomi et al, 2013). This is a potential source of predictability that can benefit midlatitude Asian countries.…”
Section: Midlatitudesmentioning
confidence: 99%
“…Kosaka et al (2012) showed that, in summer 2010, many coupled seasonal forecast models predicted a cool summer in developing La Niña conditions. Yet, they missed the interfering role of the S-R WT, which brought a record-high hot summer over the Far East (Kosaka et al, 2012;Otomi et al, 2013). From the two above-mentioned factors influencing the summer climate over the Far East, the PJ teleconnection appears to some extent (but not entirely) predictable on the seasonal time-scale, through its link with ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with reconstructed AO or NAO index may provide new information for interdecadal variability in the spring AO-EASM relationship over the past few centuries, which appears to be effected by SST in the North Pacific (e.g., Gong et al, 2011), the Indian (e.g., Gao et al, 2014), and the North Atlantic Oceans (e.g., Otomi et al, 2013). Comparisons with reconstructed AO or NAO index may provide new information for interdecadal variability in the spring AO-EASM relationship over the past few centuries, which appears to be effected by SST in the North Pacific (e.g., Gong et al, 2011), the Indian (e.g., Gao et al, 2014), and the North Atlantic Oceans (e.g., Otomi et al, 2013).…”
Section: Comparison With Reconstructed Naomentioning
confidence: 99%
“…In future work, we will extend hydroclimate reconstructions using tree-ring δ 18 O in northeastern Japan. Comparisons with reconstructed AO or NAO index may provide new information for interdecadal variability in the spring AO-EASM relationship over the past few centuries, which appears to be effected by SST in the North Pacific (e.g., Gong et al, 2011), the Indian (e.g., Gao et al, 2014), and the North Atlantic Oceans (e.g., Otomi et al, 2013). Additional comparisons with reconstructed other climate parameters (e.g., SST in the North Pacific, the Indian, and North Atlantic Oceans) also may allow us to consider whether the spatial change in spring AO-associated signals is a recent phenomenon or a more persistent characteristic of this teleconnection.…”
Section: 1029/2018gc007634mentioning
confidence: 99%